Filogenia e reclassificação de Mesitiinae (Hymenoptera, Bethylidae) - Barbosa, Diego Nunes (2013)
Mesitiini were described as a tribe of subfamily Bethylinae then later Bethylinae werepromoted to the level of what family Mesitiini consequently erected to the level of subfamily.Mesitiinae consist of 22 genera divided into four tribes. They range through the Palaearctic, Afrotropical and Oriental regions. Countless studies focusing alpha-taxonomic subfamily were made for, but none was to investigate the relationship between cladistic groupings that comprise Mesitiinae.The need for the cladistic analyses for Mesitiinae is due to the fact that the genera do not have their synapomorphies defined hence it is difficult to understand these genera. Analyses based on representative species of 22 genera (including all type-species of the genera) of the subfamily bring a resolution of cladistic relationships between groups and will explain the synapomorphies relating to these groups.For the cladistic analyses were selected 192 characters of 61 Mesitinae species and eight species relating to other Bethylidae subfamilies. As a result, 15 cladograms were obtained. Based on them, new synapomorphies and diagnosis to Mesitiinae were established; the dissolution of the tribal classification toMesitiinae was established; boundaries and synapomorphies to the genera Bradepyris, Gerbekas, Heterocoelia, Incertosulcus, Mesitius, Pilomesitius and Zimankos were established, new genus to Mesitiinae was identified; generic synonymies and combinations as consequent redefinition of the genera mentioned above were established. The results of cladistic analyses of Mesitiinae show that the genera which comprisethe subfamily have problems regarding their taxonomic delimitation and the species that compose them. This work was not able to resolve taxonomic problem concerning the genera of Mesitiinae, however, this represents a starting point for future work aimed to resolve internal problems related to Mesitiinae genera and their respective limits and synapomorphies